NFV-PEAR: Posicionamento e Encadeamento Adaptativo de Funções Virtuais de Rede - Miotto, Gustavo; Luizelli, Marcelo Caggiani; Cordeiro, Weverton Luis da Costa; Gaspary, Luciano Paschoal (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
The design of flexible and efficient mechanisms for proper placement and chaining of virtual network functions (VNFs) is key for the success of Network Function Virtualization (NFV). State-of-the-art solutions, however, consider fixed (and immutable) flow processing and bandwidth requirements when placing VNFs in the Network Points of Presence (N-PoPs). This limitation becomes critical in NFV-enabled networks having highly dynamic flow behavior, and in which flow processing requirements and available N-PoP resources change constantly. To bridge this gap, we present NFV-PEAR, a framework for adaptive VNF placement and chaining. In NFV-PEAR, one may periodically (re)arrange previously determined placement and chaining of VNFs, with the goal of maintaining acceptable end-to-end flow performance despite fluctuations of flow processing costs and requirements. In parallel, NFV-PEAR seeks to minimize network changes (e.g., reallocation of VNFs or network flows) done to fulfill this goal. The results obtained from an experimental evaluation provide evidence that NFV-PEAR has potential to significantly reduce the number of network changes required to ensure end-to-end flow performance, thus ensuring stable operation of network services.